A 'Pacific renaissance'?: Exploring the Pacific diaspora in Aotearoa New Zealand through the evolution of festivals and popular music. Issue 2 (1st November 2015) - Mackley-Crump, Jared
The post World War II large-scale migration of Pacific peoples to Aotearoa New Zealand represents one of the country's most significant demographic changes of the late twentieth century. Communities were first established in the main centres before gradually expanding and becoming entrenched across the country. With the passing of new generations, these communities became primarily locally born and/or raised. This article addresses the growth of Pacific festivals over four decades and argues that this development demonstrates cultural and diasporic evolution. It also posits that, by focusing on the changing nature of music within the festival space, these processes are further illuminated. From their beginnings in the 1970s as spaces of purely traditional musics, Pacific festivals experienced significant growth from the 1990s as part of a 'Pacific renaissance'. This period saw a coming-of-age of the first New Zealand-born generations and fused with a reaction against the preceding marginalization of Pacific communities. As part of this renaissance, popular music increasingly became an important medium through which notions of diasporic identity and culture were negotiated, and the role of popular music within festival spaces likewise evolved. Popular music is now central in a sonic landscape that incorporates both traditional and popular musics as representative of the Pacific diaspora and its cultural evolution and continued negotiation in twenty-first century New Zealand.